2021
DOI: 10.1177/26318318211047832
|View full text |Cite
|
Sign up to set email alerts
|

The Cyber Avatar of Sexual Harassment at the Workplace: Media Analysis of Reports During COVID-19

Abstract: Background: Whether working at physical workplaces or from the seeming safety of home, women employees continue to be hounded by sexual harassment. During COVID-19, sexual harassment has taken on a cyber avatar and continues to enjoy the protections afforded by ambiguity and inept implementation. Objectives: The study explores how media reported cyber sexual harassment (CSH) during a 1-year period after COVID-19 in India. It explores the dominant discourses evident in such media reports, such as the ways in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Such measures included the shift to working from home [ 39 ] via telecommunication tools such as email, phone, chat, and video apps. Whether working in physical workplaces or the apparent safety of home, researchers [ 40 ] have suggested that women employees continue to be chased by sexual harassment. Thus, sexual harassment has taken the new form of a cyber avatar [ 40 ] and remains unnoticed due to the protections afforded by ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…Such measures included the shift to working from home [ 39 ] via telecommunication tools such as email, phone, chat, and video apps. Whether working in physical workplaces or the apparent safety of home, researchers [ 40 ] have suggested that women employees continue to be chased by sexual harassment. Thus, sexual harassment has taken the new form of a cyber avatar [ 40 ] and remains unnoticed due to the protections afforded by ambiguity.…”
Section: Discussionmentioning
confidence: 99%